Upaya Guru Pendidikan Agama Islam dalam Memperbaiki Perilaku Menyimpang Sosial Siswa di SMP Negeri 22 Padang - Ike Febriani; Indah Muliati (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
This study aims to find out how the efforts of PAI teachers in improving students' social deviant behavior at SMP Negeri 22 Padang, the first is what are the forms of social deviant behavior of students at SMP Negeri 22 Padang, what are the causal factors in students' social deviant behavior at SMP Negeri 22 Padang , and how the efforts of PAI teachers in improving students' social deviant behavior at SMP Negeri 22 Padang. This research is a research using qualitative methods, with a case study approach. Sources of data from this study were three informants through interviews consisting of PAI teachers, BK teachers, and students at SMP Negeri 22 Padang. The data collection techniques of this research are observation, interviews, and documentation. The data analysis technique used is data reduction, data presentation and conclusion drawing. The data validation technique is by using source triangulation. The results of this study indicate that the efforts of PAI teachers in improving social deviant behavior at SMP Negeri 22 Padang are: First: related to the form of social deviant behavior of students at SMP Negeri 22 Padang, namely: a) being rude to teachers, b) saying rudely, c) carrying cellphones going to school, d) not collecting PAI assignments, e) skipping school. Second, there are three factors that cause students' social deviant behavior, namely: a) family factors, b) friend factors. c) community environmental factors. Third, regarding the efforts of PAI teachers in improving students' social deviant behavior, there are three, namely: a) preventive efforts, b) repressive efforts, and c) curative efforts.